METHODOLOGICAL CHARACTERISTICS OF COMPARATIVE ASSESSMENT OF AVIATION TRAINER’S - Самков, О.В.; Корнієнко, О.В.; Височанський, А.С.; Качур, С.Ю. (Science-based technologies, 2009)
The article is designed to consider the question of elaboration systematic foundations of aviation trainer’s com-parative appreciation and creation the proper algorithm.